Rutherford Chang. The Record Collector as Artist-Curator - Drobnick, Jim (Revue musicale OICRM)

(untitled) (Observatoire interdisciplinaire de création et recherche en musique (OICRM), 2023)
Record collectors judge their acquisitions by condition and rarity. Artist Rutherford Chang undermines such norms by seeking as many copies as possible, in whatever state, of one of the best-selling albums of all time: The Beatles (1968), or “the White Album.” After 50+ years, many of the 3 million numbered albums have become worn due to handling but also because of writing and drawing. Since 2013, the artist has accumulated over 3,200 copies—most that are chafed, scribbled upon, stained, or moldy. This article examines Chang’s project and its interrogation of fan appreciation and practices of consumption; the affects of aging and patina; the notion of collaborative creativity; and the role of the artist-curator. In amassing such a diverse array, We Buy White Albums highlights the variability of a mass-produced commodity while demonstrating the effectiveness of an artist-curatorial methodology to raise issues about the life and care of record albums.